Opini Mahasiswa Kota Medan Terhadap Iklan Politik Calon Gubernur Dan Wakil Gubernur Sumatera Utara Tahun 2018 - Faizal Hamzah Lubis (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
Research on opinion a student of the city of medan political for the commercial future governors and vice governors north sumatra years 2018 using the quantitative methods with the approach correlational analysis. Percent of the population in this research as many as 1994 students. By the use of the withdrawal of in the entire household sample as presented arikunto by taking 10 % of the total number of, so that we have been selected sample been disclosed in the research that event as many as 200 people. This research result indicates that the message political that was delivered through outdoor media in right at the point received kindly by the respondents, even 73,00% of respondents said advertising outdoor media we made every living being a belief in themselves among respondents to determining voting patterns scare information out of political. In addition there are 59,00 % the number of respondents who when they split asunder and 17,00% respondents found it affected against a choice a significant proportion of respondents political from a d to political outdoor media which was conveyed by candidate couple .